Pembelajaran IPS di Era Digital: Pemanfaatan Platform E-Learning di Sekolah Dasar - Saqjuddin Saqjuddin (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Pancasila education plays The transformation of education in the digital era has significantly shifted learning paradigms, including in the context of Social Studies (IPS) instruction at the elementary school level. The implementation of e-learning platforms has emerged as a strategic alternative to enhance the quality, effectiveness, and relevance of Social Studies learning in line with 21st-century educational demands. This article aims to analyze the utilization of e-learning platforms in elementary Social Studies education by highlighting the opportunities, challenges, and impacts on both the learning process and student outcomes. A descriptive qualitative approach was employed, drawing on recent literature from national and international journals, educational policy documents, and relevant research findings. The results indicate that e-learning fosters greater student participation, motivation, and engagement through interactive, visual, and collaborative approaches. Digital platforms such as Google Classroom, Moodle, and Edmodo provide features that support project-based learning, online discussions, and authentic assessment practices. However, several challenges persist, including limited infrastructure, low digital literacy among teachers and students, and unequal access to technology. Therefore, integrative strategies are required, including teacher training, the development of contextual digital teaching modules, and strong collaboration among schools, parents, and government stakeholders. The findings underscore the importance of e-learning not merely as an alternative medium but as an integral component of an inclusive and sustainable transformation in Social Studies education. This study is expected to serve as a reference for policymakers and educational practitioners in designing adaptive and future-ready Social Studies learning models in the digital age.